2021
DOI: 10.21037/qims-20-1095
|View full text |Cite
|
Sign up to set email alerts
|

Predicting radiation pneumonitis with fuzzy clustering neural network using 4DCT ventilation image based dosimetric parameters

Abstract: Background: To develop a fuzzy clustering neural network to predict radiation-induced pneumonitis (RP) using four-dimensional computed tomography (4DCT) ventilation image (VI) based dosimetric parameters for thoracic cancer patients. Methods:The VI were retrospectively calculated from pre-treatment 4DCT data using a deformable image registration (DIR) and an improved VI algorithm. Similar to dose-volume histogram (DVH) of intensity modulated radiotherapy (IMRT), dose-function histogram (DFH) was derived from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…If a point is found with the bestimproved value of distortion function, the new data point will replace the current best data point. These newly generated best data points form the new medoids (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…If a point is found with the bestimproved value of distortion function, the new data point will replace the current best data point. These newly generated best data points form the new medoids (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…RP is a well-known complication in thoracic radiotherapy. Several studies have investigated the predictive dosimetric factors for RP risk during thoracic radiotherapy (21)(22)(23)(24). For treatment-related pneumonitis, the classic predictors considered are V5, V20, and the mean lung dose (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Fuzzy theory possesses significant advantage in dealing with uncertain problems [ 18 ]. FCM algorithm is an unsupervised image segmentation method widely applied in image segmentation [ 19 , 20 ], and it is characterized by high sensitivity as well as accuracy and wide application in medical field. Joloudari et al [ 21 ] applied FCM deep neural network (FCM-DNN) in cardiac magnetic resonance CAD imaging dataset and found out that the accuracy of the proposed FCM-DNN model reached 99.91%, which indicated that the model achieved the optimal performance.…”
Section: Discussionmentioning
confidence: 99%